Gnostičeskij spasitel´ ili "revnostnyj hristianin"? - Zabukovec, Urša (Slavistična revija, 2014)
The article discusses the ideas of a famous contemporary Russian dostoevskologist Karen Stepanjan about the protagonist of "The Idiot" as an imposter, who wants to redeem the world by taking the sins of others upon himelf. Stepanjan believes the reason Myshkin does not succed in this mission is his distorted perception of reality. Our analysis of the novel, however, casts doubts on Stepanjan's conclusions and more or less agrees with the so called "tradicional" reading of the novel.
Keywords: "Idiot"; Dostoevskij, Fedor Mihajlovič, 1821-1881; literarne študije; literarni junaki; literary characters; Myshkin; ruska književnost; ruski pisatelji; Russian literature; Russian writers; Stepanjan, Karen